A Religious Approach to Modern Management - Keita SUGIYAMA; Hiroaki KANEKO; Hideki ISHIDA; Andra GROSU; George MOISE (Communications of International Proceedings, 2022)
Religion and business are two concepts so divergent that it is highly unlikely to be seen in the same context. Due the complexity of these concepts, any collision between them creates even more complex phenomena worth studying. Religion is an undeniable macro force influencing business, society and geographic environments. Stakeholders of both religion and business are connected through myriads of threads, ranging from the visible specter of open, well intended and driven components of corporate social responsibility partnerships, to a deeper and less transparent web of ties, mostly unspoken and highly contextualized. This paper aims to narrow down the key aspects of the relationship between business and religion and monitor the functionality and uniqueness of a management system based on religious principles in traditional Japanese organizations.
Keywords: Business; Japan; culture; motivation; ethics; religion; management.